A Variant of sNASP Exacerbates Lymphocyte Subset Disorder and Nephritis in a Spontaneous Lupus Model Sle1.Yaa Mouse. (21st October 2021) - Zhang, Jianye; Du, Xiaoping; Wang, Hui; Bao, Yatao; Lian, Meng; Xu, Zhiwei; Ju, Jiyu
Abstract : A variant of somatic nuclear autoantigenic sperm protein (sNASP) was identified from the murine lupus susceptibility locus Sle2c1 by whole exome sequencing (WES). Previous studies have shown that mutant sNASP could synergize with the Fas lpr mutation in exacerbating autoimmunity and aggravating end-organ inflammation. In the current study, the sNASP mutation was introduced into Sle1.Yaa mice to detect whether it has a synergistic effect with Sle1 or Yaa loci. As expected, compared with Sle1.Yaa mice, Sle1.Yaa. Δ sNASP mice showed enlarged lymph nodes, aggravated renal inflammation, and shortened survival time. The proportions of CD3 + T cells, activated CD19 + CD86 + B cells, Th1 cells in the spleen and lymph nodes, and Th17 cells in lymph nodes in Sle1.Yaa. Δ sNASP mice were increased compared to those in Sle1.Yaa mice. The levels of IFN- γ and TNF- α in the serum of Sle1.Yaa. Δ sNASP mice were higher than those of Sle1.Yaa mice. The above results show that mutant sNASP can interact with different lupus susceptibility genes and promote the disease process of systemic lupus erythematosus.